A series of typical and atypical cases of Bazex syndrome: Identifying the red herring to avoid delaying cancer treatment. Issue 11 (15th July 2020) - Eckstein, Jacob; Healy, Erin; Jain, Angita; Hawkins, Daniel; Ho, Quoc‐Anh; Agrawal, Amit; Ozer, Enver; Rupert, Robert; Diavolitsis, Virginia M.; Bhatt, Aashish D.
Abstract: Bazex syndrome is a rare paraneoplastic dermatosis that precedes diagnosis of cancer. Awareness of this syndrome is important, as it allows early detection of underlying malignancy and may prevent misdiagnosis and delays in cancer treatment. Abstract : Bazex syndrome is a rare paraneoplastic dermatosis that precedes diagnosis of cancer. Awareness of this syndrome is important, as it allows early detection of underlying malignancy and may prevent misdiagnosis and delays in cancer treatment.